Komunikasi Interpersonal Umat Hindu Dengan Non Hindu Di Dusun Badung Desa Malaka Kecamatan Pemenang Kabupaten Lombok Utara - I Made Puja Artana; I Wayan Wirata; Ni Luh Aryani (Program Studi Magister S2 Ilmu Komunikasi Hindu Institut Agama Hindu Negeri Gde Pudja Mataram, 2019)
Unity among religious people shows evidence of compromise, where all religions uphold the values ​​of peace and humanity. However, because there are different religious understandings, conflicts between religious communities and internal religious communities can be anticipated based on a human and family approach. This research is a descriptive qualitative research conducted in Badung Hamlet, Malaka Village, Pemenang District, North Lombok Regency. Types and sources of data are primary and secondary data. Data collected by observation, interview and documentation. Furthermore, the data were analyzed with data reduction techniques, data display and data verification. The data from the analysis results are presented by following the method of writing the enhanced spelling. Based on research conducted, obtained research results that show that the interaction or interpersonal communication of Hindus with non-Hindus in Badung Hamlet, Malaka Village, Pemenang District, North Lombok Regency is well established. The forms of interaction that occur between minority Hindus and non-Hindus in carrying out religious activities are the Associative Form and the Dissociative Form. Factors that influence Hinduism in carrying out religious life in a minority environment are religion, self-image, image of others and social environment. The impact of social interaction carried out by Hindus with non-Hindus is positive and negative on social life in the environment.